Relationship between respiratory muscle strength and weightlifting capacity in weightlifters - Pipat, C.; Weerapong, C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction Inspiratory muscle strength has been shown to be improved by weightlifting training (1). However, there were no reports concerning the role of respiratory muscle strength on lung function and weightlifting performance. The main purpose of this study was to determine the role of inspiratory and expiratory muscle strength on spirometric lung function and weightlifting capacity in weightlifters. The effect of belt wearing on weightlifting performance was also investigated. Methods A group of nine collegiate male weightlifters (WL) (aged 16.8±0.4 y) of different weightlifting performance and the age-and body weight-matched healthy sedentary control group (C) (aged 16.7±0.5 y) volunteered as subjects. Inspiratory and expiratory muscle strength were indicated by maximal static inspiratory (PImax) and expiratory pressure (PEmax), respectively, measured at different lung volumes (i.e. residual volume, RV; functional residual capacity, FRC; and total lung capacity, TLC) by using a respiratory pressure meter under the guidelines recommended by the ATS/ERS (2). A spirometric lung function test of forced vital capacity (FVC) and forced expiratory volume in 1 sec (FEV1) was performed in each subject under the guidelines recommended by the ATS (3). Comparison of the respiratory muscle strength and lung function between WL and C was performed. Weightlifting capacity was assessed in three weightlifting types (i.e., snatch, clean and jerk, and isometric) by the maximum weight each subject could lift. Results The FVC (3.80±0.26 l) and FEV1 (87.96±1.2% FVC) of the WL and those of the control (3.76±0.15 l and 91.2±1.9% FVC, respectively) were comparable. The FVC/body height of the two subject groups (2.30+0.14 l/m for WL and 2.06±0.11 l/m for C) were also similar. WL had greater PImax at FRC (155.0±8.9 cmH2O, p<0.01) and at RV (172.1±8.8 cmH2O, p<0.01) than those of C. The PImax at FRC and at RV of the C were 110.3±4.3 and 120.4±4.4 cmH2O, respectively. The greater PEmax at FRC (173.2±10.0 cmH2O, p<0.01) and at TLC (192.4±12.3 cmH2O, p<0.01) of WL than those of C were also observed. The PEmax at FRC and at TLC of the C were 121.7±4.2 and 132.3±4.4 cmH2O, respectively. The differences in these respiratory pressure parameters expressed relative to body weight between the two subject groups were also significant. In the WL group, snatch lifting capacity was positively correlated (p<0.05) with PImax. The relationship between isometric weightlifting capacity, either with or without weight belt, and PImax was also found (p<0.05). However, clean and jerk lifting capacity, either with or without belt, was not related to PImax. No significant correlations between PEmax and the capacity of any types of weightlifting could be observed. Among the three types of weightlifting, isometric type showed the highest lifting capacity either with or without belt. The capacity for isometric weightlifting with belt was 161.6±6.1kg and without belt was 149.4±5.2kg.In this study the athletes wore a weight belt only during clean and jerk and isometric lifting. Wearing the belt could enhance the capacity for both types of lifting being tested (p<0.01).The percent enhancement by belt was greater in clean and jerk than isometric weightlifting. Discussion / Conclusions The present study indicates that weightlifters had greater respiratory muscle strength than sedentary control. The weightlifters with greater inspiratory muscle strength exhibited higher capacity in isometric and snatch but not clean and jerk weightlifting. A decrease in lung volume brought about by wearing a weight belt was associated with an increase in weightlifting capacity. Our findings suggested that inspiratory muscle strength might play an important role on weightlifting performance in low or moderate biomechanically dependent weightlifting type. Wearing a weight belt could improve the performance in any types of weightlifting.